PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPUASAN PELANGGAN PADA JASA PENGIRIMAN JALUR DARAT: STUDI PADA JNE CABANG PONOROGO - Megasari, Laksita Dini; Rapini, Titi; Purwaningrum, Titis (Gapenas Publisher, 2024)
Expedition or delivery services have become a service that is growing quite rapidly in the era of globalization, the flow of information and increasingly high consumption needs, as well as the development of online shop or e-commerce businesses have resulted in an increase in the use of expedition services. This research uses a quantitative approach, namely data that can be calculated in the form of numbers. This research using quantitative methods is intended to determine the influence of service quality on customer loyalty which is mediated by customer satisfaction in land delivery services (Study at JNE Ponorogo Branch). The author's data analysis begins with collecting and processing data in the form of a closed questionnaire with a Likert scale where alternative answers with a value of 1 to 5 are scored based on answers to good questions regarding Service Quality (X), Customer Loyalty (Y1) and Customer Satisfaction (Y2). Based on the results of the discussion according to the data managed using the multiple linear regression analysis model, it is concluded that; Service Quality influences Customer Loyalty. So in this research Service Quality is needed to increase the work productivity of companies and customers. Service Quality influences Customer Satisfaction. So in this research Service Quality is needed to increase Customer Satisfaction of JNE Ponorogo Branch. Customer Satisfaction influences Customer Loyalty. So in this research the Customer Satisfaction variable is able to increase Customer Loyalty. Customer Satisfaction is able to mediate the influence of Service Quality on Customer Loyalty. So in this research the Customer Satisfaction variable is able to mediate Service Quality on Employee Work Productivity. So the role of Customer Satisfaction as a mediating variable on the affective aspects and Customer Loyalty of JNE Ponorogo Branch is very necessary